PENGARUH UKURAN PERUSAHAAN, LEVERAGE, SALES GROWTH, DAN UMUR PERUSAHAAN TERHADAP TAX AVOIDANCE - Richie; Yustina Triyani (Jurnal Akuntansi, 2023)
This study aims to identify and examine the effect of firm size, leverage, sales growth, and firm age to tax avoidance on manufacturing company listed in Indonesia stock exchange for the period 2016 – 2018. Method of sampling used in this study is non-probability sampling with purposive sampling technique, and got 31 observation data. The data analysis technique used is: pooling test, classical assumption test, F, t and R2 test. The result of this study conclude that firm size and leverage have positive effect on tax avoidance, whereas sales growth and firm age hav negative effect on tax avoidance.